Effects of Continuous Cropping of Sweet Potato on the Fungal Community Structure in Rhizospheric Soil - Gao, Zhiyuan; Han, Meikun; Hu, Yaya; Li, Ziqian; Liu, Chaofang; Wang, Xue; Tian, Qing; Jiao, Weijing; Hu, Jianmin; Liu, Lanfu; Guan, Zhengjun; Ma, Zhimin (Frontiers in Microbiology, 2019)
Soil microorganisms play an important role in the ecosystem, and have a certain relationship with the continuous cropping obstacles, which are common with sweet potato. However, there are few reports on the effects of continuous cropping of sweet potato on the microbial community structure in the rhizospheric soil. Here, we investigated the effects of continuous cropping of sweet potato on the fungal community structure in rhizospheric soil, in order to provide theoretical basis for prevention and control of continuous cropping obstacles. This study used X18 and Y138 varieties as experimental materials. Soil samples were collected during the early period of planting and harvest in two consecutive years, and fungi were analyzed using Illumina Miseq. Results showed that the fungi diversity and richness in rhizospheric soil of X18 and Y138 were significantly increased after continuous cropping; the most dominant fungi phylum was Ascomycota, which decreased significantly after continuous cropping. In addition, the content of beneficial fungi such as Chaetomium was reduced, while that of harmful fungi such as Verticillium, Fusarium, and Colletotrichum were increased. The composition of X18 and Y138 fungal community in the same sampling period after continuous cropping was similar, although that of the same sweet potato variety significantly differed with the sampling period. Overall, our results indicate that continuous cropping alters the fungal community structure of the sweet potato rhizospheric soil, such that the content of beneficial fungi decrease, while that of harmful fungi increase, thereby increasing soil-borne diseases and reducing the yield and quality of sweet potato. Furthermore, these effects are different for different sweet potato varieties. Thus, during actual production, attention should be paid to maintain the stability of sweet potato rhizospheric soil micro-ecology through rotation or application of microbial fertilizers and soil amendments to alleviate continuous cropping obstacles.